BASE: the Baryon Antibaryon Symmetry Experiment - Smorra, Christian; Blaum, Klaus; Bojtar, L.; Borchert, M.; Franke, K.A.; Higuchi, T.; Leefer, N.; Nagahama, H.; Matsuda, Y.; Mooser, A.; Niemann, M.; Ospelkaus, C.; et al. (European physical journal special topics, 2015)
The Baryon Antibaryon Symmetry Experiment (BASE) aims at performing a stringent test of the combined charge parity and time reversal (CPT) symmetry by comparing the magnetic moments of the proton and the antiproton with high precision. Using single particles in a Penning trap, the proton/antiproton g-factors, i.e. the magnetic moment in units of the nuclear magneton, are determined by measuring the respective ratio of the spin-precession frequency to the cyclotron frequency. The spin precession frequency is measured by non-destructive detection of spin quantum transitions using the continuous Stern-Gerlach effect, and the cyclotron frequency is determined from the particle*s motional eigenfrequencies in the Penning trap using the invariance theorem. By application of the double Penning-trap method we expect that in our measurements a fractional precision of δg/g 10−9 can be achieved. The successful application of this method to the antiproton will consist a factor 1000 improvement in the fractional precision of its magnetic moment. The BASE collaboration has constructed and commissioned a new experiment at the Antiproton Decelerator (AD) of CERN. This article describes and summarizes the physical and technical aspects of this new experiment.
Gesehen am 18.06.2020